LEARNING BY USING MDSOLIDS SOFTWARE ON MECHANICS OF MATERIALS COURSE FOR IMPROVING LEARNING OUTPUT AND INDEPENDENCE LEARNING OF STUDENT MECHANICAL ENGINEERING EDUCATION SARJANAWIYATA TAMANSISWA UNIVERSITY YOGYAKARTA - Setuju Setuju; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aims to determine the effect of using mdsolids software mechanics materials course to improve learning outcomes and learning independence of student Mechanical Engineering Education Sarjanawiyata Tamansiswa University of Yogyakarta.This research was conducted with quasi-experimental methods. The results of the study were collected with the test group, and analyzed by t-test. Independence of student learning during the lesson observed, further analyzed by calculating the gain scores.The results of the t test of the difference test provides information that the average achievement of the experimental group was significantly different from the control class. The results of the experimental class learning better than the control class. Students who use the software program Mdsolids in mechanics of materials courses after having observed an increase in independent learning and learning at each end of the five overall aspects of the independence of the measured category has a high learning independence with an average achievement score on the five aspects of learning independence of 0, 73.